13-week dietary study and in vitro and in vivo genotoxicity studies of a structuring fat produced through a microalgal fermentation process. (2016) - Matulka, R.A.; Chan, T.; Green, R.; Carney, J.R.; Franklin, S.; Licari, P.
Highlights: The dietary safety of a unique microalgal structuring fat produced by a heterotrophic fermentation process was assessed. The algal fat was non-mutagenic in Salmonella typhimurium and Escherichia coli tester strains at up to 5000 μg/plate. The algal fat was non-clastogenic in mouse bone marrow after a single oral dose at 2000 mg/kg bw. Dietary NOAEL of the algal structuring fat for rats in a 13-week study was 100 000 ppm, the highest concentration tested. Based on consumption, the oral NOAEL for the algal structuring fat in rats was 5299 (male) and 6313.8 (female) mg/kg bw/day. Abstract: Microalgae are increasingly being utilized as food ingredients for a variety of applications, including as sources of protein, egg and dairy substitutes, and cooking oils. The dietary safety of a new structuring fat produced using a heterotrophic fermentation process by a strain of Prototheca moriformis was evaluated in a 13-week dietary toxicity study and compared with kokum fat, a structuring fat of similar composition used in the food industry and derived from Garcinia indica seeds. The algal structuring fat was evaluated for its genotoxic potential using both in vitro and in vivo assays. No treatment-related adverse events occurred in rats consuming algal structuring fat or kokum fat in the 13-week study; no treatment-related effects were reported for body weight, food consumption, urinalysis, hematology, clinical chemistry, gross pathology, organ weights, or histopathology. While statistically significant effects occurred in some parameters, none were dose-related or considered adverse. Overall, the NOAELs for the algal structuring fat and the kokum fat were 100 000 ppm, the highest concentrations tested. The algal structuring fat was not mutagenic in the bacterial reverse mutation assay in the Salmonella typhimurium or Escherichia coli strains tested and was not clastogenic in the in vivo mouse bone marrow chromosome aberration assay.